Depression in heart failure. (2nd June 2019) - Sharp, John; McCowat, Monica
Abstract: Heart failure is one of the most prevalent long-term physical health conditions. It is suggested that up to 26 million people are living with it worldwide including approximately 920 000 people in the UK. Evidence has consistently demonstrated the links between cardiac health and mental health; therefore, this article will explain depression and its presentation in heart failure, as these two conditions have been strongly and consistently linked. The prevalence of depression in heart failure will be reviewed from epidemiological studies and an overview of the impact of comorbid depression in heart failure will be provided, with a particular focus on mortality, morbidity and quality of life outcomes. The relationship between depression and heart failure will be discussed by examining pathophysiological and behavioural mechanisms, as well as evidence regarding the appropriate identification and subsequent management of heart failure depression will be reviewed.